Polar Remote Sensing Volume I: Atmosphere and Oceans - Lubin, Dan; Massom, Robert (Geophysical Sciences, 2006)
This book is a comprehensive discussion of the applications of both satellite remote sensing and advanced ground-based remote sensing as related to polar science and operations. It discusses the various passive and active remote sensor types before concentrating on specific geophysical applications. Its interdisciplinary approach - including atmospheric chemistry, meteorology, climate and radiation balance, sea-ice studies, physical oceanography, glaciology, ecology and hydrology - means that major advances and publications are highlighted, together with the state of the art in each area. Polar Remote Sensing describes satellite remote sensing applications to all polar-related disciplines provides suggestions for applications of satellite remote sensing to polar research contains significant new information on Earth's polar regions discusses sophisticated, ground-based remote sensing applications summarises fundamental principles of detectors, imaging and geophysical product retrieval.